(untitled) (translation. a transdisciplinary journal, 2022)
Translation editor Siri Nergaard and editorial board member Edwin Gentzler met with Gayatri Chakravorty Spivak for an informal conversation during the 201 1 Research Symposium organized by the Nida School of Translatio in Studies in New York City (September 14). As one of the symposium’s two principal lecturers, Spivak gave the speech "Gender and Translation in the Global Utopia," a transcribed version of which was published in issue 1 of translation under the title "Scattered Speculations on Translation Studies."